2021
DOI: 10.1177/23337214211050807
|View full text |Cite
|
Sign up to set email alerts
|

Deprescribing Statins and Proton Pump Inhibitors in Nursing Home Residents; a Pragmatic Exploratory Study

Abstract: Introduction Polypharmacy is common in the frail nursing home population and associated with an increased risk of adverse events, unplanned hospitalizations, and increased all-cause mortality. Deprescribing using a deprescribing algorithm might reduce unnecessary polypharmacy. This exploratory study was performed to determine the effect of this implicit deprescribing algorithm in deprescribing statins and proton pump inhibitors (PPIs) in nursing home residents. Method Multicenter, longitudinal, single-arm expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, based on our data, NSAIDs are only rarely used, as well as the prevalence of main gastrointestinal diagnoses should be low. Moreover, differences with other countries suggest that Italian nursing homes should implement deprescribing initiatives on PPIs, taking advantage of relevant evidence from original studies and authoritative guidelines ( Visser et al, 2021 ; Onder et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, based on our data, NSAIDs are only rarely used, as well as the prevalence of main gastrointestinal diagnoses should be low. Moreover, differences with other countries suggest that Italian nursing homes should implement deprescribing initiatives on PPIs, taking advantage of relevant evidence from original studies and authoritative guidelines ( Visser et al, 2021 ; Onder et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on changing physician behavior has revealed promise of such multifaceted interventions [ 64 – 66 ], but it is impossible to ascribe intervention success to one component like education if more intervention functions are used. For enablement, very consistent positive effects were observed [ 12 , 38 , 39 , 41 , 44 , 47 , 48 , 51 62 ]. These effective interventions mostly focused on deprescribing and involved algorithms, quality check improvements and involvement of pharmacists.…”
Section: Discussionmentioning
confidence: 83%
“…Intervention studies ( n = 55, 74%) comprised of longitudinal studies in which a policy change was evaluated (prospectively or retrospectively) as well as studies that evaluated a specific intervention as part of the study itself. The majority of these studies included publication or dissemination of (new) guidelines [ 36 , 37 ], implementation of algorithms [ 38 , 39 ], and pharmacist oversight or interventions [ 40 , 41 ].…”
Section: Changing Ppi Prescription Behaviormentioning
confidence: 99%
See 1 more Smart Citation